2021
DOI: 10.1155/2021/3961445
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Role of Natural Endocrine Disruptors: Phytoestrogens in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common form of dementia with a growing incidence rate primarily among the elderly. It is a neurodegenerative, progressive disorder leading to significant cognitive loss. Despite numerous pieces of research, no cure for halting the disease has been discovered yet. Phytoestrogens are nonestradiol compounds classified as one of the endocrine-disrupting chemicals (EDCs), meaning that they can potentially disrupt hormonal balance and result in developmental and reproductive abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 157 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…Despite the ill-famed status, endocrine disruptors are increasingly recognized for their numerous beneficial effects [60]. Phytoestrogens, found naturally in plants and foods, are a type of endocrine-disrupting chemical considered safe for consumption and use in moderation [61].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ill-famed status, endocrine disruptors are increasingly recognized for their numerous beneficial effects [60]. Phytoestrogens, found naturally in plants and foods, are a type of endocrine-disrupting chemical considered safe for consumption and use in moderation [61].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the confirmed participation of PEs in the regulation of the cell cycle and apoptosis via ERs, these ER-independent activities cause PEs to possess antioxidant, antiproliferative, antimutagenic, and antiangiogenic properties [117,118]. In clinical practice, this scenario translates into better or worse documented potential health benefits, including the alleviation of menopausal symptoms (e.g., hot flashes, night sweats, sleep problems, and mood changes) and a reduced risk of osteoporosis, heart disease, neurodegenerative processes, and breast cancer [46,[119][120][121][122]. This last effect is still somewhat controversial because some clinical studies have reported data that suggest that isoflavones may increase breast cancer incidence in sensitive individuals via their estrogenic and proliferative effects [123][124][125].…”
Section: Signaling Not Mediated By Ers-a Significant Source Of Differ...mentioning
confidence: 99%
“…Some of these phytoestrogens activate the nuclear factor erythroid 2‐related factor 2 (NRF2) and its gene targets, which are regulated by antioxidant response element (ARE). The activation of NRF‐2/ARE pathway induces the production of several antioxidant enzymes including catalase (CAT), glutathione peroxidase (GPx), heme oxygenase‐1 (HO‐1), NAD(P)H dehydrogenase (quinone 1) (NQO1) and superoxide dismutase (SOD) (Domańska et al, 2021) (Figure 2d).…”
Section: Mechanisms Of Neuroprotective Effects Of T Pratense and Its ...mentioning
confidence: 99%